Liberia : Request for Disbursement under the Rapid Credit Facility-Press Release; Staff Report; and Statement by the Executive Director for Liberia. (IMF Staff Country Reports; Country Report ;, 2020)
This paper presents Liberia's Request for Disbursement Under the Rapid Credit Facility. The economic impact of the pandemic is hitting the poorest with little social safety net, and food security of those relying on uncertain daily income is a pressing concern. The authorities have responded by taking revenue and expenditure measures to support emergency food aid for the poor; improving monitoring and control of spending; and safeguarding scarce foreign exchange reserves. Preliminary data suggest that performance under the Extended Credit Facility-supported program has been weak, though the authorities are fully committed to address the weaknesses. In order to address the shortage of Liberian dollars and the growing need for more US dollar liquidity, the authorities have contracted the printing of additional Liberian dollar bank notes and are formulating measures for inclusion in the FY2021 budget to augment US dollar liquidity.